Penyelesaian Hadhānah Pasca Perceraian dalam Putusan Hakim Pengadilan Tinggi Agama Nomor:005/Pdt.G/2018/pta.Plg - Ifrohati Ifrohati; Erniwati Erniwati; Mea Santia Wati (Universitas Islam Negeri Raden Fatah Palembang, 2022)
The obligation to care for children does not end even if the parents are divorced. However, there is often a struggle over child custody, even having to involve a court to resolve it. One of them was the hadhanah case at PTA Palembang with decision Number: 005/Pdt.G/2018/PTA.plg. which will be the focus of this study. The purpose of this study is to examine the judge's decision in terms of Law Number 17 of 2016 and Islamic Law, so that a comparison between the two can be known. This research is a normative juridical research. The approach method is comparative. The data analysis technique that the writer uses is a qualitative descriptive analysis technique. In decision Number: 005/Pdt.G/2018/PTA.plg. Child custody is handed over to anyone because the lawsuit contains a formal defect so that the lawsuit cannot be accepted. According to Islamic law, hadhanah rights as stated in decision Number: 005/Pdt.G/2018/PTA.plg. handed over to the mother, but Law Number 17 of 2016 does not question this. This law stipulates that children must be cared for by their own parents, unless there are other justified reasons.